Semantic Dispersion In Translation Of The Qur'an Into Malay/ التَّشتُّت الدَّلالي في ترجمة القرآن إلى اللُّغة المالايوية - Yeob, Shamsul Jamili Bin; Balki, Nur Nazwan; Alosman, Abdulrahman (Ijaz Arabi Journal of Arabic Learning, 2024)
The issue of semantic dispersion has captured the attention of researchers in the field, and they attribute its reasons to translators’ negligence in highlighting the connotations correctly. This is a result of their sole reliance on literal or meaningful translation that consequently led to ambiguity surrounding the meanings and semantic style of Quranic verses. This study aimed to analyze the process of translating words in selected Quranic verses into the Malay language by different translators of the holy Qur’an by identifying the main problems involved in the translation process. Comparisons were made between the translations above by selecting several controversial verses that lead to semantic dispersion. The current study employed the descriptive analytical comparative approach, where the researchers described the approaches in translating the holy Qur’an from the Arabic language into the Malay language. Three translations were compared, namely the Al-Humaira translation (printed version) and the other two translations, which are digital, namely Surah.my and The Noor, because the Malay community commonly uses them. Al-Humaira is the primary source in this study, where examples of selected verses were analyzed and compared with the other two translations. Several findings were reported in this study, with the most important being that there are glaring differences with significant gaps between the translation processes of the translations above, where the translation of Al-Humaira was better and more accurate than the other two translations. Another finding in this study is that the difficulties facing translators are related to the connotations of meanings resulting from dimensions of language such as culture and connection to context, difficulties that cast a shadow over all translation processes. Hence, it is almost impossible to convey the meanings of the holy Qur’an with complete accuracy despite the excellent skills of translators in the field.